Performance of some mainland trees and palm species planted in the coastal islands of Bangladesh - Islam, SK Ahiul; Miah, Md Abdul Quddus; Habib, Md Ahsan; Moula, Md Golam (Journal of the Asiatic Society of Bangladesh, Science, 2014)
Considering the sustainability of coastal forests, a trial with 13 mainland tree species was conducted at Rangabali island of Patuakhali district and Char Kukri-Mukri island of Bhola district to observe the site-suitability and growth performance of the species. Another experiment of 4 palm species was conducted in a foreshore area at Char Kukri- Mukri island. On the basis of survival, height and diameter growth, Samanea saman (Jacq.) Merr. (rain tree), Casuarina equisetifolia Forst. (jhao), Pithecellobium dulce Benth. (payra), Albizia lebbeck (L.) Benth. (kala koroi) and Albizia procera (Roxb.) Benth. (sada koroi) at Rangabali; and P. dulce, Acacia nilotica (L.) Willd. (babla), S. saman and C. equisetifolia at Char Kukri-Mukri were found promising. Among the palm species, Cocos nucifera L. (coconut), Phoenix sylvestris Roxb. (date palm) and Borassus flabellifer L. (palmyra palm) showed good growth performance in the foreshore area. Therefore, these promising mainland trees and palm species are suitable for raising large scale plantations in the raised coastal lands of Bangladesh. J. Asiat. Soc. Bangladesh, Sci. 40(1): 9-14, June 2014